Transfer and business taxation law and jurisprudence : with the national revenue code of 1977 as amended up to Republic Act No. 9337 - Aralar, Reynaldo B (Mandaluyong City, Philippines, 2007)
As the global spiraling of oil products continues, the expanded value added tax is now being implemented. The Philippine government is confronted with the choice of implementing unpopular and pocket hurting tax measures or face international lenders constraints if the taxes were not imposed and efficiently corrected
Keywords: Business tax; Inheritence and transfer tax- law and legislation- philippines